2010
DOI: 10.1002/jcu.20706
|View full text |Cite
|
Sign up to set email alerts
|

Fetal bowel calcifications: A sign of anal atresia with rectourethral fistula

Abstract: Fetal bowel calcifications were observed at 24 weeks of gestation in a male fetus, suggesting an anorectal malformation (ARM) with rectourethral fistula. At birth, the newborn presented with complex ARM including anal atresia, rectourethral fistula, and esophageal atresia. The prenatal sonographic visualization of calcifications within distended bowel should raise the suspicion of ARM including anal atresia and rectourethral fistula, the presence of such calcification depending on the timing of onset of fistul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…Intraluminal calcifications were mentioned as an additional sonographic marker for AA. These calcifications represent enterolithiasis, which is the result of solidification and condensation of stacked meconium. However, this is a quite rare clinical manifestation and therefore not very useful for prenatal diagnosis of AA.…”
Section: Discussionmentioning
confidence: 99%
“…Intraluminal calcifications were mentioned as an additional sonographic marker for AA. These calcifications represent enterolithiasis, which is the result of solidification and condensation of stacked meconium. However, this is a quite rare clinical manifestation and therefore not very useful for prenatal diagnosis of AA.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, anorectal atresia is detected only after birth. Brantberg et al reported that the prenatal detection rate for this condition is low (15.9%) because diagnostic signs are mostly indirect, such as bowel dilatation and intraluminal calcifications . The low percentage of detection can be attributed to the difficulty in ultrasound (US) evaluations of the fetal anal sphincter and rectum as well as a lack of awareness among sonographers regarding the typical US signs of this condition.…”
mentioning
confidence: 99%
“…In our case, there was a similar abdominal mass initially, but this mass regressed significantly by 27 weeks' gestation as the hydro(metro)colpos and ascites developed. Whether the initial mass in our case represented urachus or simply bowel is unclear but intraluminal calcifications are reportedly seen in cases of imperforate anus as early as the second trimester, and bowel dilation as early as 12 weeks' gestation . If the mass was bowel, why it essentially resolved by the time the ascites developed is not clear, but its echogenic appearance favors bowel rather than urachus.…”
Section: Discussionmentioning
confidence: 80%